Case report: Recurrent syncope as initial symptom in a patient with neck lymphoma - Wu, Yanfang; Yang, Deyan; Sun, Luxi; Xu, Xiqi; Gao, Peng; Cheng, Kangan; Chen, Taibo; Cheng, Zhongwei; Liu, Yongtai; Fang, Quan (Frontiers in Cardiovascular Medicine, 2022)
Syncope may have many different causes, requiring careful identification. Recurrent syncope is uncommon as an initial symptom of neck lymphoma. Head and neck tumors involving the carotid artery cause syncope associate with carotid sinus syndrome. We report the case of a 72-year-old man who suffered from recurrent syncope due to compression of the right carotid sinus by diffuse large B-cell lymphoma and was successfully treated with immunochemotherapy. Syncope may be an early or sole sign of a neck or head tumor. We should be aware of the possibility of an underlying malignancy in patients with unexplained syncope after initial evaluation.